Lafutidine-Induced Increase in Intracellular Ca2+ Concentrations in PC12 and Endothelial Cells - Kana Kunieda; Akiyoshi Someya; Syunji Horie; Hirofusa Ajioka; Toshihiko Murayama (Elsevier, 2005)
Lafutidine, a histamine H2 receptor antagonist, exerts gastroprotective effects in addition to gastric antisecretory activity. The gastrointestinal protective effects of lafutidine are mediated by capsaicin-sensitive neurons, where capsaicin excites neurons by opening a member of the transient receptor potential channel family (TRPV1). Since the effect of lafutidine on the intracellular Ca2+ concentration ([Ca2+]i) in cells has not been elucidated, we investigated the lafutidine response to [Ca2+]i in rat pheochromocytoma PC12 and human endothelial cells. Lafutidine at pharmacological concentrations greater than 1 mM induced a sustained increase in [Ca2+]i in the presence of extracellular CaCl2 in PC12 cells, while capsaicin showed dual effects on [Ca2+]i in PC12 cells, where it activated TRPV1 and inhibited store-operated Ca2+ entry. The thapsigargin (an activator of store-operated Ca2+ entry)-induced increase in [Ca2+]i in PC12 cells was inhibited by capsaicin and SKF96365, an inhibitor of store-operated Ca2+ entry, and the lafutidine response was inhibited by capsaicin but not by SKF96365. In endothelial cells, lafutidine induced an increase in [Ca2+]i in a SKF96365-insensitive manner. These results suggest that lafutidine stimulates Ca2+ entry via the capsaicin-sensitive pathway but not the SKF96365-sensitive pathway. The possible role of store-operated Ca2+ entry induced by lafutidine on gastrointestinal function is also discussed. Keywords:: lafutidine, intracellular Ca2+ concentration, PC12 cell, human umbilical vein endothelial cell, store-operated Ca2+ entry